A bibliometric analysis of literatures in terms of WHO maternal morbidity definition - CHEN Meiyi; QIAN Xu (Shanghai yufang yixue, 2022)
ObjectiveThis study used bibliometrics to analyze the global application and research progress of the new WHO maternal morbidity definition.MethodsA Total of 13 literatures published by WHO-MMWG since 2013 were collected， and a total of 249 citing references were identified by reference retrieval. Bibliometric method was used to analyze the distribution of the publication time， types， journals， authors， publication location， research location， research field and keywords through BibExcel and VOSviewer.ResultsThe number of the citing references showed a wavy increase. Gecatti J G was the author with the most publications （17）. Universidade Estadual de Campinas and the WHO Human Reproduction Programme were the two main author groups. Brazil was the study site with the most original research （21）. Pilot studies of Maternal WOICE tools have been conducted only in Brazil and Africa. Among the citing references， 26.1% of the research fields focused on obstetrics and gynecology， and 73.9% of the literature involved other research fields. There was no “non-severe maternal morbidity” as keywords in the literatures. The word “severe maternal morbidity” and “maternal near miss” had the highest number of co-occurrence （13）， Words related to postpartum mental health were new keywords， and related research is gradually increasing.ConclusionThere would be still a lot of research contents based on the WHO maternal morbidity definition. Maternal WOICE Tools has not piloted in high-income regions and China. The definition and concept of “non-severe maternal mortality” was not found in the literature， neither were the global consensus on the definition of “severe maternal mortality”. Postpartum mental health has become a research hotspot in recent years.